The Impact of Financial Crisis on Earnings Management Activities: Evidence from Jordan - Muneer Shana’a, Areej; Abdel Halim AlKhalaileh, Mahmoud; Mohammad Abu Rumman , Ghaleb (Jordan Journal of Business Administration, 2023)
This study examined empirically the earnings management practices of Jordanian firms during the financial crisis. The study used a sample of 568 observations (firm-year) related to 71 non-financial firms listed in Amman Stock Exchange (ASE) over the 8-year period (2005-2012). Correlation and OLS regression analyses are used to test the study's predictions. The study reports a negative, but statistically insignificant, association between earnings management activities and the financial crisis. This result does not provide sufficient support for the study’s predictions and most prior studies’ findings which report a decrease in earning-management practices during the financial crisis. Consistent with most prior related studies, the study findings indicate that firm’s size and CFO are inversely related to earnings management activities, while leverage is positively related to earnings management. Failure to detect a significant relationship between the financial crisis and earnings management activities by this study could be primarily due to the minimal impact of the finical crisis on Jordanian firms compared to firms operating in well-developed economics documented by prior studies. The study’s findings could be useful for policy makers, regulators, managers, investors and other capital providers within the Jordanian environment.